Area of center of pressure in closed eye setting as a measure of postural sway: Association with frailty and functional capacity in older adults with diabetes - Remi Kodera; Yoshiaki Tamura; Yuji Murao; Fumino Yorikawa; Ai Iizuka; Kazuhito Oba; Kenji Toyoshima; Yuko Chiba; Joji Ishikawa; Atsushi Araki (PLoS ONE, 2025)
Older adults with diabetes mellitus are at a higher risk of frailty, which can lead to disability and death; therefore, effective frailty screening is necessary in such populations. However, evidence linking sway meter indices to frailty or functional capacity remains limited. This cross-sectional study aimed to investigate the association of postural stability, assessed using a sway meter, with frailty and functional capacity in older patients with and without diabetes. Data from 362 older outpatients (149 with diabetes and 213 without) who visited the Frailty Clinic between 2021 and 2022 were analyzed. The Kihon Check List was used to define frailty and the Short Physical Performance Battery to assess functional capacity. The sway meter indices included locus length (Lo) and area of the center of pressure (Ao) with open eyes, locus length (Lc) and area of center of pressure (Ac) with closed eyes, and the Romberg ratio (Ac/Ao). Univariate and multivariate analyses were performed to determine associations. All sway meter indices were higher in patients with diabetes. In this group, Lo, Ao, and Ac levels were significantly higher in those with frailty, while Lo, Lc, Ao, and Ac levels were higher in those with low functional capacity. Receiver operating characteristic analyses showed that Ao and Ac had relatively high area under the curve for both diagnoses. Binominal logistic regression analyses revealed that Ac was significantly associated with frailty in patients with diabetes after adjusting for age, sex, HbA1c, cognitive function, number of medications, and several diabetic complication indices, including loss of Achilles tendon reflexes (odds ratio, 1.107; 95% confidence interval, 1.001–1.225; p = 0.048). Ac was also significantly associated with low functional capacity. These findings suggest that the area of the center of pressure, especially in a closed-eye setting, is associated with frailty and functional capacity in older adults with diabetes.